Anticancer Effects of Cyclocarya paliurus Polysaccharide (CPP) on Thyroid Carcinoma In Vitro and In Vivo. (27th December 2018) - He, Zhiwei; Lv, Fangfang; Gan, Yueli; Gu, Jing; Que, Ting
Abstract : In this study, we explored the role and mechanisms of Cyclocarya paliurus polysaccharide on cell apoptosis in thyroid cancer (TC) cells. The apoptosis of thyroid cancer cells in vitro and tumor tissues in vivo induced by Cyclocarya paliurus polysaccharide was determined by MTT assay and flow cytometric assay. The downstream molecules including phosphop-protein kinase B (p-Akt), Akt, B-cell lymphoma 2 (Bcl-2), and Bcl-2-associated X protein (Bax) in tumor tissue were evaluated by western blotting. MTT and flow cytometry assay in vitro revealed Cyclocarya paliurus polysaccharide-induced apoptosis of thyroid cancer cell line in a manner of time-dependent and dose-dependent. In vivo assay showed 50 mg/kg and 100 mg/kg Cyclocarya paliurus polysaccharide significantly suppressed the proliferation of thyroid cancer in mice. Western blotting showed downregulation of p-Akt, Akt, and Bcl-2 and upregulation of Bax. These results suggest that Cyclocarya paliurus polysaccharide may enhance thyroid cancer cell apoptosis by suppressing the activation of p-Akt, Akt, and Bcl-2 and activating Bax, which provide a novel use of CPP as a thyroid cancer treatment.